2017
DOI: 10.1111/lam.12792
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic effect and postantibiotic sub-MIC effect of LTX-109 and mupirocin on Staphylococcus aureus blood isolates

Abstract: Resistant bacterial infections continue to be a challenge for clinicians. Identification of antibiotics with pharmacodynamic advantages may be beneficial in the treatment of these infections. An antibiotic with a longer postantibiotic effect may be able to be administered less frequently resulting in improved adherence. In this study, a new synthetic antimicrobial peptide, LTX-109, demonstrated a more prolonged time for LTX-109 than mupirocin against methicillin-resistant Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…It is one of the characteristics of pharmacodynamics being increasingly applied to the design of dosing regimens of antimicrobial agents. The inhibition in growth of the pathogen is followed by recovery and regain of their infectious potential, once the efficacy of antimicrobial agent was finished/reduced ( Saravolatz et al, 2017 ). Figure 1 suggested that S. aureus growth was delayed post 2 and 4 h treatment at two different concentrations of peptide-Ba49.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the characteristics of pharmacodynamics being increasingly applied to the design of dosing regimens of antimicrobial agents. The inhibition in growth of the pathogen is followed by recovery and regain of their infectious potential, once the efficacy of antimicrobial agent was finished/reduced ( Saravolatz et al, 2017 ). Figure 1 suggested that S. aureus growth was delayed post 2 and 4 h treatment at two different concentrations of peptide-Ba49.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the damage to the cell could be immense and might take a long time to repair. In comparison, a naturally produced AMP DLP4 from hemolymph of Hermetia illucens has been reported to have a PAE value of 8.83 h against S. aureus ( Li et al, 2020 ), and also a synthetic AMP, LTX-109, was shown to have 5.51 h of PAE against S. aureus ( Saravolatz et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the so called "post-antibiotic sub-MIC effect" (PA-SME) is the phenomenon most closely related to PAEP. In contrast to PAEP, which involves two different agents, PA-SME results in sensitization to an antibiotic at subinhibitory concentrations after exposure to the same compound at concentrations above its MIC [47][48][49][50][51][52]. Similarly, increased bacterial susceptibility to phagocytosis or intracellular killing by leukocytes during the PAE phase was described by McDonald and collaborators, which defined this phenomenon as Post-antibiotic Leukocyte Enhancement (PALE) [53].…”
Section: Discussionmentioning
confidence: 99%
“…LTX-109 (LTX109, Lytixar, LTX 109) is an AMP peptidomimetic (Arg-Tbt-Arg-NH-EtPh) that was in clinical development by Lytix Biopharma AS. LTX-109 contains 2 arginine residues, a central modified tryptophan residue (2,5,7-tri( tert -butyl)tryptophan) and an ethylphenyl group at the C-terminus ( 242 ) with antibacterial ( 243 , 244 ) and antifungal activity ( 245 ). LTX-109 was fungicidal against S. cerevisiae (MIC 8 mg/L), causing a 3 log kill within 60 min, and was also active against pre-formed S. cerevisiae biofilms.…”
Section: Novel Antifungal Peptides In Clinical and Preclinical Develomentioning
confidence: 99%